FinTech adoption and financial inclusion: Evidence from household consumption in China - Yang, Tong; Zhang, Xun (Journal of banking & finance, 2022)
This paper provides micro-level evidence on how FinTech adoption affects household consumption and consumption inequality. Our hypothesis is that through FinTech's payment facilitation and credit constraint alleviation, higher FinTech adoption by households fosters financial inclusion by promoting consumption. Financial inclusion is especially increased for households that traditionally consumed less, which suggests that FinTech could reduce consumption inequality. By combining region-level FinTech adoption measures with household-level representative data of consumption, we find that higher FinTech adoption by a household increases household consumption and reduces consumption inequality across households. Using the distance to Hangzhou from the city in which a household is located as an instrument variable to capture the exogenous variation in FinTech adoption yields results with similar economic and statistical significance. In addition, traditional financial infrastructure is still a prerequisite for the benign distributive impacts provided by FinTech credit, which demonstrates the need for further welfare-improving policies. Our paper adds to the literature by documenting FinTech to be a market force that contributes to financial inclusion.